Atributos do solo em função dos diferentes usos em perímetro irrigado do Sertão de Pernambuco - SANTOS, Patrícia Ribeiro dos (2010)
The semiarid Northeast Brazil, represented by the Caatinga biome is characterized as an environment of low water availability and shallow soils, which require regional scientific community, further studies directed at understanding and managing these resources, for their preservation in a sustainable way. Thus, this study aims to evaluate the chemical, physical and biological soil of Irrigated Perimeter Icó-Mandantes. The perimeter includes an irrigated area of 1.300 hectares distributed in agricultural lots that have records of information on the type (s) of crop (s), irrigation system, use of fertilizers and pesticides, the batch production situation, identification of area so degraded. Using the map of soil classification of Irrigated Perimeter Icó-Mandantes were selected for the study areas separating the soil by the clay content, as follows:Class 1 - soils with clay content below 9%, Class 2 - Soil with clay content of 9 and 15%, and Class 3 - soils with clay content above 15%. Uses studied were classified as short-cycle crops (C), FRUTICULTURA (F), pasture (P) and native vegetation (V).Addition was built to study further treatment, consisting of the discarded lands (D). Soil samples were collected randomly selected plots, according to the use and soil class and surrounding areas with no history of agricultural use, to compare with the properties of soil incorporated into the process of using manmade and compare the different agricultural uses. Soil samples were analyzed for the chemical, physical and biological.Data were submitted to descriptive statistics and multivariate analysis (principal component analysis and clustering). Observed changes in the chemical, physical and biological analysis in all uses. For soils with clay content below 9%, using F showed the greatest similarity to V, with less disruption of the attributes studied, grouping by electrical conductivity smaller, more balanced levels of exchangeable cations and a lower density, and better conditions for soil microbes. In soils with clay contents between 9 and 15%, the introduction of irrigated agriculture promoted increases insoluble Na content and decreased soil microbial activity in all uses studied. The use of soil carbon had higher levels of salinity in relation to the area of native vegetation,resulting in the reduction of microbial activity and microbial biomass carbon in thethree classes of soils studied. The analysis of soil classes in all uses studied, resulted in separation by class of soil, confirming that the granulometric composition of soil is one factor that should be considered in the selection of management practices of soil and water irrigation.